ID055 Health Stakeholder Mapping, essential strategies for success: An integrative review: EIXO 2: IMPLEMENTAÇÃO DE TECNOLOGIAS E DIRETRIZES CLÍNICAS EM SAÚDE - Fernandes Nunes, Talita; Vinicius Falcão Paiva dos Santos, Pedro; Ferreira Lopes, Mariana; Brant, Jonas (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2024)
Introduction The mapping of health stakeholders is a crucial activity for the effective management of projects and interventions in the health sector. It is an essential tool in the health area, allowing the identification and integration of these actors in strategic planning and improving the relationship with them. Thus, identifying and understanding the various actors involved in an initiative allows for improved communication, increased engagement, and obtaining the necessary support to achieve the proposed objectives, especially in public health emergencies. Methods In this study, we explore essential strategies for conducting successful stakeholder mapping, as well as identifying insights into how stakeholder mapping is performed by health professionals and managers in public health emergencies. Data were collected from pre-selected databases, and the collection stage was performed by pairs in a “blind” manner. The literature retrieval process was carried out in two phases. To sort the articles, the acronym PICO was used as a criterion: Population (health professionals and managers), Intervention (challenges to mapping stakeholders), Context (emergency situations in public health), and Outcome (outcome) (improve the process of stakeholder mapping). Results The integrative review resulted in 1844 articles and showed that these strategies play a crucial role in decision-making in health, by understanding the needs, expectations, and influences of stakeholders on policies and projects. In public health, stakeholder mapping is even more relevant, being crucial to face challenges and improving the quality of life of populations. In emergencies, this tool makes it possible to coordinate and communicate effectively, protecting the health of the affected population. To improve the mapping process, it is necessary to adopt systematic approaches, considering the needs of the stakeholders and promoting the participation of all. Ongoing assessment is key to getting better results and improving practices. Discussion and conclusions In conclusion, this study recommends stakeholder mapping as a valuable instrument for the health sector, contributing to its continuous development, improving services, and the quality of care provided to the community. Its development and application not only improve the management of health projects and interventions but also plays a key role in optimizing the functioning and constant evolution of the Unified Health System (SUS) in Brazil, allowing the active participation of those involved in the formulation of policies, strategic planning, and decision-making. The inclusion of stakeholders, or key actors, in the process of defining priorities and guidelines contributes to more transparent and responsible governance, resulting in a health system that is more agile and adaptable to the needs of the population.